Finance, uncertainty and investment: assessing the gains and losses of a generalized non linear structural approach using Belgian panel data - Marcel Gérard; Frédéric Verschueren (National Bank of Belgium, 2002)
Using panel data for 2,329 Belgian firms observed between 1985 and 1999, this paper aims at getting a better understanding of Belgian firms' investment behavior. Two main and interrelated topics are investigated: the link between financial structure and investment decision, on the one hand, the effect of uncertainty on the level of investment, on the other hand. Such research sets forth the effect of some key variables, both in terms of level and volatility. The study is conducted within a structural approach but reduced form equations are also estimated. A generalised dynamic effect is investigated by introducing adjustment costs related through time. From that study, it clearly appears that small firms and high debt level firms are more sensitive to interest rate and cash flow. However, no role for investment price volatility is observed.
Keywords: C23; C33; E22; 330; Investment; debt constraint; panel data; GMM; Kapitalstruktur; Investitionsentscheidung; Betriebsgröße; Zins; Cash Flow; Belgien